(untitled) (Praxis Educativa, 2026)
This article is a case study that analyzes the role of field trips as a teaching strategy at the Colegio Científico de Costa Rica, Puntarenas Campus. The study collects data by administering questionnaires to 5 teachers and 37 students, as well as a semi-structured interview with the school’s executive. The results show that field trips are a valuable pedagogical tool that allows for establishing links between the theory and practice of classroom content, fostering meaningful learning and strengthening students’ scientific competencies and soft skills. Furthermore, the article analyzes the challenges that field trips could generate and their negative impact on students and teachers. The objective is to obtain an overview of the implementation of this teaching strategy based on the experience of this educational institution, which can offer recommendations based on its experience and that may be useful to other educational centers.